ANALISIS PRODUKSI BERSIH UNTUK MENURUNKAN JUMLAH DAN KONSENTRASI TOTAL SUSPENDED SOLID (TSS) DAN CHEMYCAL OXYGEN DEMAND (COD) DALAM LIMBAH CAIR DI INDUSTRI WINGKO HAYU, BANTUL - , ARIYANI ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Wingko (coconut based food) production processes generate solid and liquid wastes. Solid waste has been utilized while the wastewater in large numbers and have not been handled properly. On the other hand, wastewater treatment such as wastewater plant need much costly. Therefore, efforts are needed to reduce the amount and concentration of waste for example is cleaner production application. The purpose of this study is to determine the work stations that most generate wastewater and to determine good housekeeping alternative techniques that provide most reduction of liquid waste in number and concentration.. The research was conducted by measuring the mass balance of production, determining the factors causes wastewater using a cause effect diagram and to determine cleaner production alternatives such as good housekeeping alternative. Then, feasibility of alternatives are analyzed in technical and economics. Good housekeeping techniques that has been done are first combination is application of standard operating procedures with giving baseline for coconut, second combination is separation between raw materials and waste and giving baseline for coconut, then third combination is application of standard operating procedures and separation of raw materials and waste. Based on the research shows the most amount of waste generated at the work station of coconut washing is 50.65 liters every batch, COD concentration 366.20 mg/L and TSS of 1817.43 mg/L. Application of combination are first combination results obtained decrease the amount of waste produced by 54.71%, COD concentration decreased 73,71% and TSS concentration decreased 64.17%